A conceptual framework for the relationship between formal and informal learning - Rohs, Matthias (Swiss Journal of Educational Research, 2018)
Increasing importance is presently being devoted to informal learning. In this context, this article discusses the relationship among formal, non-formal and informal learning. Based on different arguments for a stronger interdependence between formal and informal learning, the conceptual and definitional backgrounds of the relationships of formal, non-formal and informal learning are described and clarified. Following, the paper presents mediating processes between these learning modes, as well as the conditions that foster their interactions and make them constructive. The paper thus provides a basis to think educational practices and to found empirical research in this field.